Virtual monoenergetic images preserve diagnostic assessability in contrast media reduced abdominal spectral detector CT - Lennartz, Simon; Große Hokamp, Nils; Zäske, Charlotte; Zopfs, David; Bratke, Grischa; Glauner, Andreas; Maintz, David; Persigehl, Thorsten; Chang, De-Hua; Hickethier, Tilman (British journal of radiology, 2020)
Objectives:To investigate if low-keV virtual monoenergetic images (VMI40keV) from abdominal spectral detector CT (SDCT) with reduced intravenous contrast media application (RCM) provide abdominal assessment similar to conventional images with standard contrast media (SCM) dose.Methods:78 patients with abdominal SDCT were retrospectively included: 41 patients at risk for adverse reactions who received 44 RCM examinations with 50 ml and 37 patients who underwent 44 SCM examinations with 100 ml of contrast media (CM) and who were matched for effective body diameters. RCM, SCM images and RCM-VMI40keV were reconstructed. Attenuation and signal-to-noise ratio (SNR) of liver, pancreas, kidneys, lymph nodes, psoas muscle, aorta and portal vein were assessed ROIs-based. Contrast-to-noise ratios (CNR) of lymph nodes vs aorta/portal vein were calculated. Two readers evaluated organ/vessel contrast, lymph node delineation, image noise and overall assessability using 4-point Likert scales.Results:RCM were inferior to SCM images in all quantitative/qualitative criteria. RCM-VMI40keV and SCM images showed similar lymph node and muscle attenuation (p = 0.83,0.17), while for all other ROIs, RCM-VMI40keV showed higher attenuation (p ≤ 0.05). SNR was comparable between RCM-VMI40keV and SCM images (p range: 0.23-0.99). CNR of lymph nodes was highest in RCM-VMI40keV (p ≤ 0.05). RCM-VMI40keV received equivalent or higher scores than SCM in all criteria except for organ contrast, overall assessability and image noise, where SCM were superior (p ≤ 0.05). However, RCM-VMI40keV received proper or excellent scores in 88.6/94.2/95.4% of the referring cases.Conclusions:VMI40keV counteract contrast deterioration in CM reduced abdominal SDCT, facilitating diagnostic assessment.Advances in knowledge:SDCT-derived VMI40keV provide adequate depiction of vessels, organs and lymph nodes even at notable CM reduction.